O empirismo naturalista de Quine e a indeterminação da tradução - Acríssio Luiz Gonçalves (2021)
Since Willard V. O. Quine introduced the thesis of the indeterminacy of translation in Word and Object (1960), it has become the source of numerous debates. However, its formulation and philosophical consequences are still misunderstood. Given this scenario, I aim to uncover and analyze the theoretical basis supporting it. In the first chapter, I present Quine's motivations for establishing the indeterminacy of translation by taking as point of departure the debates with Rudolf Carnap about the notion of meaning. Subsequently, I show the difference between the indeterminacy of reference and the holophrastic indeterminacy by means of empirical examples and a discussion of recent objections to the thesis. In the second chapter, I evaluate the indeterminacy of translation from the point of view of the naturalism that permeates Quine's work, and I argue that we have good reasons to abandon the mentalist notion of meaning and adopt a semantic theory that explains the meaning of the statements grounded in the linguistic behavior of the speakers. In the third chapter, I discuss the influence of behaviorism on the formulation of the indeterminacy of translation, but argue that Quine minimizes his commitment to the behaviorist perspective. Finally, given the naturalism that characterizes Quine’s philosophy, I argue that it is empiricism that grounds the thesis.